2000
DOI: 10.1159/000045710
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urinary Albumin Excretion and Glomerular Filtration Rate in Normotensive, Nonproteinuric Patients with Type 2 Diabetes mellitus

Abstract: Background/Aim: In patients with type 2 diabetes mellitus, the relationship between glomerular filtration rate (GFR) and urinary albumin excretion remains an unresolved issue. In order to investigate the early renal function abnormalities, GFR and urinary albumin excretion were assessed, and their relationship was examined in normotensive patients with type 2 diabetes mellitus. Methods: In a cross-sectional study of 85 nonhypertensive Japanese patients with type 2 diabetes mellitus not showing overt proteinuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…Similar changes have been demonstrated in white patients, with hyperfiltration present in 16% of 110 previously untreated type 2 diabetic patients [12]. Further cross-sectional studies measuring GFR isotopically have also demonstrated hyperfiltration in various racial groups [13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 59%
“…Similar changes have been demonstrated in white patients, with hyperfiltration present in 16% of 110 previously untreated type 2 diabetic patients [12]. Further cross-sectional studies measuring GFR isotopically have also demonstrated hyperfiltration in various racial groups [13][14][15][16][17].…”
Section: Introductionsupporting
confidence: 59%
“…In diabetic patients, it has been proved that glomerular hyperfiltration plays a critical role in the initiation and progression of diabetic glomerulopathy. 13,15,16 In some cases, the increase of glomerular filtration can even precede MA. 16 With the disease progression, MA progresses to macroalbuminuria and GFR declines, so resolved glomerular hyperfiltration may not necessarily reflect a ''normalized'' GFR, but rather implicate a clinically important loss of filtration capacity in patients with MA.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,16 In some cases, the increase of glomerular filtration can even precede MA. 16 With the disease progression, MA progresses to macroalbuminuria and GFR declines, so resolved glomerular hyperfiltration may not necessarily reflect a ''normalized'' GFR, but rather implicate a clinically important loss of filtration capacity in patients with MA. 12 Several methods of calculating GFR using endogenous creatinine, 23 Tc-pentectate 28 have been described in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we found that a characteristic feature of normotensive recipients with microalbuminuria was an increase in single kidney GFR for grafts after transplantation. The GFR of microalbuminuric patients with type 2 diabetes mellitus was significantly higher than non‐microalbuminuric and non‐diabetic patients 24 . Eberhard et al .…”
Section: Discussionmentioning
confidence: 96%